PENGARUH KAPASITAS KOMUNIKASI PEMASARAN PADA KINERJA PEMASARAN PELAKU USAHA GULA SIWALAN DI KABUPATEN SUMENEP - Manaf, Ach. Haris Abdi; Lasinta, Megafirmawanti; Andawiyah, Robi’atul (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
Marketing communication has a vital role in developing MSMEs, especially in MSME producers of siwalan sugar. However, marketing communication remains a hurdle in the development of siwalan sugar MSMEs in Prenduan Village. This is due to the still weak capacity of human resources in implementing marketing communication, as well as the lack of information about siwalan sugar in the marketing process. This research aims to describe the capacity of marketing communication, analyze the factors affecting the capacity of marketing communication among siwalan sugar entrepreneurs, and analyze the impact of marketing communication capacity on marketing performance. This research is quantitative supported by qualitative data. The research uses a census method with 45 respondents. The results show that the capacity of siwalan sugar entrepreneurs is in the moderate category. Analysis of the capacity of siwalan sugar entrepreneurs is conducted by categorizing capacity into aspects of knowledge (cognitive), attitude (affective), and action (psychomotor). The characteristics of the business are factors that influence the marketing communication capacity of the entrepreneurs. In addition, the capacity of marketing communication affects the marketing performance of siwalan sugar SMEs.